Symptomatic imperforate Cowper's syringocele in a 5-year-old boy - Roić, Goran (Radiology and oncology (Ljubljana), 2005)
Background. Cowper's syringocele is a rare anomaly in childhood. It is caused by the obstruction of the duct of Cowper's gland. Depending of the type and size of the syringocele, and the age of the patient, the treatment for symptomatic lesions could be endoscopic deroofing or open perineal surgery. Case report. We report a case of symptomatic imperforate syringocele in a 5-year-old boy. Although the syringocele are usually best shown on voiding cysto-urethrography, there was not any detectable extrinsic impression or filling defect in the bulbar urethra. Ultrasonography guided perineal puncturewith contrast filling of the cystic lesion was used to detect the connection of the Cowper's duct to the ventral surface of bulbar urethra. Conclusions. In imperforate syringocele, ultrasonography could be useful imaging technique especially in young patients, to evaluate urethra and perineal lesions and for percutaneous guided procedures.
Keywords: Abnormalities; Bulbourethral Glands; Bulbouretralne žleze; child; Child, Preschool; Ciste; Cysts; diagnostika; otroci; Otrok predšolski; Ultrasonography; urologija